Combine multi-dimension Bloom filter for membership queries - XIE Kun1; QIN Zheng2; WEN Ji-gang1; ZHANG Da-fang2; XIE Gao-gang3 (Tongxin xuebao)
Based on the analysis of multi-dimension Bloom filter（MDBF） presented before, a combine multi-dimension Bloom filter（CMBE） was presented. CMDBF adds a combine Bloom filter （CBF） to MDBF to assist in representing the whole element. When representing or querying an element, CMDBF needs two steps, the first step is representing or querying every attribute of the element with MDBF, the second step is combining all attributes to further represent or query the whole element with combine Bloom filter for further validation. Both theoretical analysis and experiment show that the CMDBF can support concise representation and approximate membership query of data set from multiple attrib- ute dimensions and CMDBF outperforms MDBF in false positive.